Helicobacter pylori cholesterol-α-glucosyltransferase manipulates cholesterol for bacterial adherence to gastric epithelial cells. Issue 1 (31st December 2021) - Hsu, Chung-Yao; Yeh, Jia-Yin; Chen, Chun-Ya; Wu, Hui-Yu; Chiang, Meng-Hsuan; Wu, Chia-Lin; Lin, Hwai-Jeng; Chiu, Cheng-Hsun; Lai, Chih-Ho
ABSTRACT: Helicobacter pylori infection is associated with several gastrointestinal diseases, including gastritis, peptic ulcers, and gastric cancer. Infection of cells with H. pylori is dependent on lipid rafts, which are cholesterol-rich microdomains located in the cell membrane. H. pylori cholesterol-α-glucosyltransferase (CGT) catalyzes the conversion of membrane cholesterol to cholesteryl glucosides, which can be incorporated into the bacterial cell wall, facilitating evasion from immune defense and colonization in the host. However, the detailed mechanisms underlying this process remain to be explored. In this study, we discovered for the first time that H. pylori CGT could promote adherence to gastric epithelial cells in a cholesterol-dependent manner. Externalization of cell membrane phosphatidylserine (PS) is crucial for enhancement of binding of H. pylori to cells by CGT and for cytotoxin-associated gene A (CagA)-induced pathogenesis. Furthermore, exogenous cholesterol interferes with the actions of H. pylori CGT to catalyze cellular cholesterol, which impedes bacterial binding to cells and attenuates subsequent inflammation, indicating that the initial attachment of H. pylori to cells is closely dependent on host cholesterol. These results provide evidence that CGT contributes to H. pylori infectivity and it may serve as a key target for the treatment of H. pylori -associated diseases.